2021
DOI: 10.3390/en14238029
|View full text |Cite|
|
Sign up to set email alerts
|

Towards Big Data Electricity Theft Detection Based on Improved RUSBoost Classifiers in Smart Grid

Abstract: The advent of the new millennium, with the promises of the digital age and space technology, favors humankind in every perspective. The technology provides us with electric power and has infinite use in multiple electronic accessories. The electric power produced by different sources is distributed to consumers by the transmission line and grid stations. During the electric transmission from primary sources, there are various methods by which to commit energy theft. Energy theft is a universal electric problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Cluster-analysis-based data-mining techniques, such as [11][12][13] High requirements on the quantity of the data; High computational cost Machine learning, such as [14][15][16][17][18][19][20][21][22][23] Strong non-linear mapping ability; Influence of super parameters on prediction stability Artificial intelligence algorithms, such as [24][25][26] Strong convergence; Easy to fall into local extreme value Data envelopment analysis, such as [27][28][29] Strong applicability; Wide application range This study presents a power load forecasting-based abnormal data detection method to improve the economy of electricity inspection and promote the sustainable development of electric power firms. First, an intelligent algorithm is used to optimize the parameters of ELM to improve the forecasting accuracy for the power load.…”
Section: Current Research Methods Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster-analysis-based data-mining techniques, such as [11][12][13] High requirements on the quantity of the data; High computational cost Machine learning, such as [14][15][16][17][18][19][20][21][22][23] Strong non-linear mapping ability; Influence of super parameters on prediction stability Artificial intelligence algorithms, such as [24][25][26] Strong convergence; Easy to fall into local extreme value Data envelopment analysis, such as [27][28][29] Strong applicability; Wide application range This study presents a power load forecasting-based abnormal data detection method to improve the economy of electricity inspection and promote the sustainable development of electric power firms. First, an intelligent algorithm is used to optimize the parameters of ELM to improve the forecasting accuracy for the power load.…”
Section: Current Research Methods Characteristicsmentioning
confidence: 99%
“…The model was found to perform better than a convolutional neural network and long-short-term memory network in electricity inspection. Akram et al [21] introduced a RUSBoost technique and proposed the manta ray foraging model and the bird flocking algorithm model, which improved the accuracy of electricity theft detection. Taking account of imbalance in electricity consumption data, Banga et al [22] designed a machine learning model which included six data-balancing techniques, and compared the performance of 12 classification algorithms, using the superposition ensemble algorithm to optimize the machine learning model to improve accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to improve operational efficiency, enhance grid security, improve customer service quality, and expand new business, State Grid has put forward higher requirements for the operational development of data [11][12]. According to the information system construction platform of State Grid, a business unified data platform with standardized and unified models, clean and transparent data, and flexible and intelligent analysis will be built in the future [13][14][15]. The State Grid Customer Service Center, as the execution unit of the power supply service business and the support organization of marketing decision-making, has accumulated the customer data and massive power supply service information of the whole network.…”
Section: Introductionmentioning
confidence: 99%
“…The study confirmed reasonable accuracy in detecting electricity theft using SVM. Another study by et al [18] proposed a novel convolutional neural network based (CNN) method with RUSBoost manta-ray foraging optimization and RUSBoost bird swarm algorithm for detecting electricity theft by analyzing customers' electricity consumption patterns. The proposed method included data preprocessing, feature extraction, model training, and standard or abnormal classification of electricity expenditure patterns.…”
Section: Introductionmentioning
confidence: 99%